The Aryl Hydrocarbon Receptor as an Immune-Modulator of Atmospheric Particulate Matter-Mediated Autoimmunity - O'Driscoll, Chelsea A.; Mezrich, Joshua D. (Frontiers in Immunology, 2018)
This review examines the current literature on the effects of atmospheric particulate matter (PM) on autoimmune disease and proposes a new role for the aryl hydrocarbon receptor (AHR) as a modulator of T cells in PM-mediated autoimmune disease. There is a significant body of literature regarding the strong epidemiologic correlations between PM exposures and worsened autoimmune diseases. Genetic predispositions account for 30% of all autoimmune disease leaving environmental factors as major contributors. Increases in incidence and prevalence of autoimmune disease have occurred concurrently with an increase in air pollution. Currently, atmospheric PM is considered to be the greatest environmental health risk worldwide. Atmospheric PM is a complex heterogenous mixture composed of diverse adsorbed organic compounds such as polycyclic aromatic hydrocarbons (PAHs) and dioxins, among others. Exposure to atmospheric PM has been shown to aggravate several autoimmune diseases. Despite strong correlations between exposure to atmospheric PM and worsened autoimmune disease, the mechanisms underlying aggravated disease are largely unknown. The AHR is a ligand activated transcription factor that responds to endogenous and exogenous ligands including toxicants present in PM, such as PAHs and dioxins. A few studies have investigated the effects of atmospheric PM on AHR activation and immune function and demonstrated that atmospheric PM can activate the AHR, change cytokine expression, and alter T cell differentiation. Several studies have found that the AHR modulates the balance between regulatory and effector T cell functions and drives T cell differentiation in vitro and in vivo using murine models of autoimmune disease. However, there are very few studies on the role of AHR in PM-mediated autoimmune disease. The AHR plays a critical role in the balance of effector and regulatory T cells and in autoimmune disease. With increased incidence and prevalence of autoimmune disease occurring concurrently with increases in air pollution, potential mechanisms that drive inflammatory and exacerbated disease need to be elucidated. This review focuses on the AHR as a potential mechanistic target for modulating T cell responses associated with PM-mediated autoimmune disease providing the most up-to-date literature on the role of AHR in autoreactive T cell function and autoimmune disease.